Reconfiguration Technology and Future Network Architecture - Julong Lan; Chiqiang Xing; Yuxiang Hu; Dongnian Cheng (Dianxin kexue)
As the scale enlargement of the internet and the continuous deployment of new applications,the disadvantages of the rigid IP architecture becomes increasingly evident.The reconfigurable network has drown widely attention due to its characteristics such as flexibility,scalability,adaptability and green energy.The current situation of the reconfigurable technology was detailed,then the reconfigurable network architecture and its adaptability for new applications were discussed.Finally,the green energy-saving characteristic of the reconfigurable network was also analyzed.